Analisis kecekapan teknikal firma melayu dalam sektor pembuatan Malaysia - Ismail, Rahmah; Tendot Abu Bakar, Norlinda (Universiti Utara Malaysia, 2008)
Purpose - this article aims to analyse and identify determinants of technical efficiency of Malay owned firm in the manufacturing sector. Design/Methodology/Approach - The analysis is based on 246 Malay owned firms surveyed in 2001/2002. Two levels of estimation are conducted, firstly, estimation of technical efficiency and secondly, estimating the tobit model to identify determinants of technical efficiency. Finding - The result from the first estimation shows that, in general, technical efficiency for the Malay owner firms is still at the medium level. The most efficiency sub-industry is fabricated metal, machines, electrical, and transportation equipment, whereas the least efficient is non-metalic, glass, and ceramic products. Furthermore, from the second estimation, the study are firm size and entrepreneur's level of education. Originality/Value - Studies on firms' technical efficiency particularly addressing the Malays are very limited. Most studies in this area focus on the industry in general.The finding from the study are crucial for entrepreneurs and the government. Identifying the determinants of technical efficiency may guide the Malay entrepreneurs to restructure their planning. The government, on the other hand, may learn from the findings in formulating its strategies to help the Malay entrepreneurs. Paper type - Research Paper